Pharmacokinetics of Capecitabine and Four Metabolites in a Heterogeneous Population of Cancer Patients: A Comprehensive Analysis - Jacobs, Bart A.W.; Deenen, Maarten J.; Joerger, Markus; Rosing, Hilde; Vries, Niels; Meulendijks, Didier; Cats, Annemieke; Beijnen, Jos H.; Schellens, Jan H.M.; Huitema, Alwin D.R. (CPT: pharmacometrics and systems pharmacology, 2019)
Capecitabine is an oral prodrug of the anticancer drug 5‐fluorouracil (5‐FU). The primary aim of this study was to develop a pharmacokinetic model for capecitabine and its metabolites, 5′‐deoxy‐5‐fluorocytidine (dFCR), 5′‐deoxy‐5‐fluorouridine (dFUR), 5‐FU, and fluoro‐β‐alanine (FBAL) using data from a heterogeneous population of cancer patients (n = 237) who participated in seven clinical studies. A four‐transit model adequately described capecitabine absorption. Capecitabine, dFCR, and FBAL pharmacokinetics were well described by two‐compartment models, and dFUR and 5‐FU were subject to flip‐flop pharmacokinetics. Partial and total gastrectomy were associated with a significantly faster capecitabine absorption resulting in higher capecitabine and metabolite peak concentrations. Patients who were heterozygous polymorphic for a genetic mutation encoding dihydropyrimidine dehydrogenase, the DPYD*2A mutation, demonstrated a 21.5% (relative standard error 11.2%) reduction in 5‐FU elimination. This comprehensive population model gives an extensive overview of capecitabine and metabolite pharmacokinetics in a large and heterogeneous population of cancer patients.